The Planning and Implementation of Computer-based Games for Project Risk Management Education: A Preliminary Case Study - Baccarini, David; Xia, Jianhong (Cecilia); Caulfield, G. (AJCEB/epress UTS Publishing, 2012)
This paper reports the preliminary stages of an action research project for the design, development and assessment of a computer-based game for student learning about project risk management. A computer game was created through the use of systems dynamic software (Simsoft) incorporating a land development project. The game was played by final year undergraduate construction management students who had to make decisions in identifying, assessing and managing project risks. A survey of their experience found: that most students had not experienced this form of online educational game previously in their studies despite the ubiquity of information technology for learning purposes in the university sector; there was no strong support for the idea that the acquisition of knowledge was better compared to conventional learning through lectures and books; the computer-based experience was enjoyable thus indicating it drew them into the learning environment; and student testing found they had gained understanding of the project risk management process.